Consumer Quality Index Chronic Skin Disease (CQI‐CSD): a new instrument to measure quality of care from the patient's perspective. (1st October 2015) - van Cranenburgh, O.D.; Krol, M.W.; Hendriks, M.C.P.; de Rie, M.A.; Smets, E.M.A.; de Korte, J.; Sprangers, M.A.G.
Summary: Background: Assessing quality of care from the patient's perspective is considered to be highly relevant. As a standardized instrument in dermatology was lacking, we developed a patient experience questionnaire regarding chronic skin disease care: the Consumer Quality Index Chronic Skin Disease (CQI‐CSD). Objectives: (i) To evaluate the dimensional structure of the CQI‐CSD, (ii) to assess its ability to distinguish between hospitals according to patients' experiences with quality of care, (iii) to explore patients' experiences with dermatological care and priorities for quality improvement according to the patients, and (iv) to optimize the questionnaire based on psychometric results and stakeholders' input. Methods: In a cross‐sectional study 5647 adult patients who received dermatological care in the past 12 months in 20 hospitals were randomly selected and invited to fill out the questionnaire. Results: Overall 1160 of 3989 eligible respondents (29% response rate, 30–87 per hospital) were included for analysis. The CQI‐CSD comprised seven scales with high internal consistency (Cronbach's α = 0·74–0·92). The instrument's discriminative power was limited. Patients were positive about the care provided by nurses and doctors, but the provision of information by healthcare providers, accessibility of care and patient involvement could be improved. We optimized the CQI‐CSD, resulting in a revised questionnaire containing 65 items. Conclusions: In conclusion, the CQI‐CSD is a useful instrument to measure patient experiences with dermatological care.